Comparison of PD-L1, CTR-1, VEGF, and p53 expression in sensitive and resistant epithelial ovarian cancer (EOC) patients to platinum-based chemotherapy - Perbowo, Primandono; Tjokroprawiro, Brahmana A.; Aryati, Aryati; Ariani, Grace; Kusumastuti, Etty H. (Narra J, 2025)
The current standard treatment for ovarian cancer is a combination of cytoreductive surgery and platinum-based chemotherapy; however, many patients develop resistance, leading to a high recurrence rate. The aim of this study was to analyze the expression of PD-L1, CTR-1, VEGF, and p53 in epithelial ovarian cancer (EOC) patients, comparing those sensitive and resistant to platinum-based chemotherapy. A cross-sectional study was conducted among EOC patients who underwent surgery and platinum-based chemotherapy between 2020 and 2023 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, with evaluations performed six months post-chemotherapy. The expression of PD-L1, CTR-1, VEGF, and p53 were measured using immunohistochemistry (IHC) and compared between chemotherapy-sensitive and resistant patients. A total of 65 patients were included: 31 resistant and 34 sensitive cases. The results showed higher PD-L1 expression in the resistant group compared to the sensitive group (mean combined positive score (CPS) of 0.46±0.29 vs 0.17±0.09, p<0.001). The CTR-1 expression was lower in the resistant group (immunoreactive score 2.90±1.30) compared to the sensitive group (immunoreactive score 6.82±2.68) with p<0.001. VEGF and p53 expression were also higher in the resistant group (6.68±2.59 vs 2.76±1.10 and 64.68±13.54% vs 30.15±13.06%, respectively) compared to the sensitive group, with both having p<0.001. The study suggests that increased expression of PD-L1, VEGF, and p53 and decreased CTR-1 expression are associated with platinum-based chemotherapy resistance among EOC patients. Therefore, these biomarkers might have the potential for predicting treatment responses and understanding resistance mechanisms.